(untitled) (Scientific journal of the Fergana State University, 2023)
The article deals with the difficulties encountered when translating from Uzbek into French. The Uzbek language is an agglutinative language, which means that the word consists of a root and many prefixes, affixes, suffixes and endings. French belongs to the analytical languages. grammatical relations are transmitted through functional words (prepositions, modal verbs, etc This difference creates certain difficulties in translation. In addition, there are differences in the construction of sentences: in French, the word order is direct - subject - predicate - object, and in Uzbek the order is as follows: subject - object, the predicate concludes the sentence. Phraseological units and sayings are especially difficult to translate. Our article is intended for students and teachers of the French language, which will help them in their further practice of translating from Uzbek into French and from French into Uzbek.